2020
DOI: 10.23887/ijssb.v4i3.27958
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Current Ratio, Return on Assets, Total Asset Turnover and Sales Growth on Capital Structure in Manufacturing Company

Abstract: This study aimed to determine how much effect the Current Ratio, Return on Assets, Total Asset Turnover and Sales Growth have on the Capital Structure of manufacturing companies listed on the IDX from 2016 to 2018. The research method used was descriptive method and multiple linear analysis method. The population of this study was 144 companies with a sample of these companies, namely 73. The data used were financial reports published by the Indonesia Stock Exchange through the website www.idx.co.id. The varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
2
11
0
2
Order By: Relevance
“…For every 1 unit increase in liquidity, debt decreases by 0.054 units. The effect of the negative current ratio (CR) on the capital structure (CS) is in line with the results of research from Said & Jusmansyah (2019) , Purba et al (2020) and Hidayat et al (2021) . The results of this study are different from those of Hertina et al (2022) who found that the current ratio had no effect on the capital structure.…”
Section: Regression Model Testsupporting
confidence: 86%
“…For every 1 unit increase in liquidity, debt decreases by 0.054 units. The effect of the negative current ratio (CR) on the capital structure (CS) is in line with the results of research from Said & Jusmansyah (2019) , Purba et al (2020) and Hidayat et al (2021) . The results of this study are different from those of Hertina et al (2022) who found that the current ratio had no effect on the capital structure.…”
Section: Regression Model Testsupporting
confidence: 86%
“…The impact of the total turnover of negative assets means the company's sales performance maintains its earnings as retained earnings and uses more external funds as capital. Purba et al (2020) that the total asset turnover partially does not affect the capital structure. When creditors provide long-term loans, creditors do not only see the asset rotation side but many aspects are considered.…”
Section: The Effect Of Activity On Capital Structurementioning
confidence: 95%
“…The solvency factors of short-term debt, average loan interest rates, and the structure of tangible assets have nothing to do with capital structure. (Purba et al, 2020) showed that the current ratio had a significant negative effect on capital structure.…”
Section: Graphic 1 Average Firm Size Activity (Tato) Profitability (R...mentioning
confidence: 99%
“…Hal tersebut dikarenakan perusahaan dapat menurunkan harga penjualan produk agar dapat bersaing dengan pasar sehingga walaupun penjualan meningkat namun laba tidak selalu meningkat bahkan bisa terjadi penurunan laba. Penelitian ini sejalan dengan penelitian yang dilakukan oleh Purba et al, (2020), bahwa pertumbuhan penjualan tidak berpengaruh terhadap struktur modal.…”
Section: Pengaruh Pertumbuhan Penjualan Terhadap Struktur Modalunclassified